Fakta Kemanusiaan dan Pandangan Dunia Pengarang dalam Film Farha Karya Darin J. Sallam: Kajian Strukturalisme Genetik: Humanitarian Facts and the Author's Worldview in Darin J. Sallam's Film Farha: A Study of Genetic Structuralism - Salsabila Nafisah Muthmainnah; Akmaliyah Akmaliyah; Mawardi Mawardi (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
Film, as a communication medium, serves not only as entertainment but also as a means of conveying social and humanitarian values. Darin J. Sallam's film Farha tells the story of a humanitarian tragedy set during the 1948 Nakba in Palestine. This study aims to uncover the representation of humanitarian facts and the author's worldview through a genetic structuralism approach. The method used is qualitative research with analytical descriptive techniques. Data were obtained through observation and note-taking of scenes, dialogues, and film subtitles, and then analyzed in stages of reduction, classification, and interpretation, based on the concepts of humanitarian facts and worldview. The results show that the film Farha contains two forms of humanitarian facts: individual and social. Individual facts are depicted through the inner experiences of the character Farha, including fear, loneliness, trauma, and the struggle for survival.Meanwhile, social facts are reflected in gender inequality, the loss of educational rights, military violence, and the collapse of humanitarian values due to war. In addition, Darin J. Sallam's worldview presents a humanistic perspective rooted in the collective historical experience of the Palestinian people, emphasizing the suffering and steadfastness of women and children as symbols of hope and resistance. The conclusion of this study shows that Farha's film not only represents a historical tragedy but also serves as a profound reflection on humanity, social justice, and the struggle for life. Through a genetic structuralist approach, this film is shown to be a manifestation of the relationship among literary works, social structures, and the author's worldview, informed by the historical reality of Palestinian society.